Characterization of recently isolated Newcastle disease viruses and development of inactivated vaccine using genotype VII Newcastle disease virus - AlJumaili, Oday Abdul Razzaq Abdul Wahhab (2017)
Newcastle Disease (ND) is a highly contagious and economically devastating disease of poultry in many parts of the world. At present, limited molecular epidemiological data are available regarding the causes of ND outbreaks in vaccinated chickens in commercial poultry farms. Knowing the genomic characteristics of Newcastle disease virus (NDV) infecting commercial poultry operations despite the chickens were vaccinated may give important insights on the infection dynamics of these viruses. In addition, molecular analyses at the subgenotype level and studies on the relationship of Malaysian NDVs with other isolates from around the world are lacking. Although many countries, including Malaysia maintain a stringent vaccination policy against ND, there are indications that ND outbreaks can still occur despite intensive vaccination. Virulent genotype VII NDV from China, Indonesia, Korea and Malaysia share only 82 to 87% similarity in amino acid residues of F and HN antigens respectively with B1 and LaSota vaccine strains (genotype II). While these genotype II-based vaccines prevent disease, they cannot stop viral shedding in the environment. Hence, the need for the so-called genotype-matched vaccines, which have been shown to reduce virus shedding, compared to genotype-mismatched vaccines is highly anticipated. Therefore, in the present study, a molecular epidemiological investigation is conducted to characterize six NDVs isolated from vaccinated commercial poultry flocks. To better understand the epidemiology of Newcastle disease outbreak, a partial F gene and HN gene were amplified from UPM-IBS 046/2014, UPM-IBS 060/2014, UPM-IBS 061/2014, UPM-IBS 074/2014, UPM-IBS 160/2015, and UPM-IBS 162A/2015 isolates by using conventional one step reverse transcription-polymerase chain reaction (RT-PCR) and then conducted sequence and phylogenetic analysis. Furthermore, inactivation of NDV IBS/025/2013 strain (naturally recombinant strain) by two different method i.e. Ultraviolet type C (UVC) and Binary ethylinimine (BEI), and tested the inactivation by inoculation of the inactivated virus in SPF eggs for two passages was successfully executed.Six NDV isolates which were recovered from ND outbreaks in chicken flocks in Malaysia were genotypically characterized. All the isolates had close phylogenetic relationship with previously characterized isolates from Malaysia as well as different countries within genotype VIIa, and genetically on the basis of the fusion (F) protein cleavage site. Among these, six NDV isolates showed an F protein cleavage site motif 112RRQKRF117 ,112KRRKRF117,112KRRKRF117, 112KRRKRF117112KRRKRF117,and 112KRRKRF117. In the present study, NDV IBS/025/2013 strain (a naturally recombinant virus strain) was successfully inactivated by UVC light+Riboflavin and chemical (BEI), and then passaged consecutively two times in SPF chicken embryonated eggs. Results from the virus inactivation study revealed that exposure to UVC light for 14 hours or treatment of the virus with BEI for 21 hours at 370C successfully inactivated the virus as evidenced by its inability to kill SPF chicken embryonated eggs 6 days post-inoculation in two consecutive passages. Both inactivated vaccines were emulsified in two different adjuvants, Nigella sativa oil adjuvant, and Freund's incomplete adjuvant to produce vaccines in the form of water in oil (W/O). A stable W/O vaccine with two different adjuvants was successfully formulated. To test the efficacy of each vaccine formulation, ten days old SPF chickens were randomly divided into 11 groups, with 11 chickens in each group. The first 5 groups were vaccinated with different formulations of the vaccine, but the remaining groups were vaccinated with LaSota live vaccine (+L) in different formulations. One group was kept as control. The result for in vivo experiment indicated that the BEI-black seed oil (BEI-BSO), BEI- Incomplete Freund'sadjuvant (BEI-IFA) as well as commercial vaccine, were fully protective against a virulent NDV challenge. Although all vaccinated groups had significantly lower mortality rate than unvaccinated-challenged group, full protection from death was observed in birds of group BEI-BSO, BEI-IFA, Commercial, UVC-BSO+L, UVC-IFA+L, BEI-BSO+L, BEI-IFA+L, and Commercial +L followed by group UVC-IFA with 33% mortality. Among vaccinated groups, the best results with regards to clinical signs and gross lesions were obtained in groups that were vaccinated with killed and live vaccine together, and groups of killed vaccine especially commercial and BEI-IFA; followed by group BEI-BSO with 10% morbidity. Vaccination provided high HI antibody titers in most of the vaccinated groups excluding UVC-BSO and UVC-IFA. The chickens in all vaccinated-challenged groups shed the challenge virus from day 3 days post challenge. Insignificant differences were observed in the frequencies of virus detection among vaccinated groups (UVC-BSO and UVC-IFA) and positive control with different incidence. Duration of virulent virus shedding in infected birds of vaccinated groups were different. Vaccination programs used in groups of killed and live vaccine have shortened the duration of virus shedding (only at 3 days post challenge), while control group and UVC-BSO group started from day 3 post challenge continued to shed the virulent virus in the feces until the end of the experiment. Meanwhile the UVC-IFA started to shed the virus from day 5 post challenge until the end of the experiment. Finally, the BEI-BSO, BEI-IFA and commercial groups started to shed the virus from day 7 post challenge until the end of the experiment with reduced titer at 10days post challenge. The measurement of potency for the inactivated vaccine BEI-BSO and BEI-IFA by the use of the mortality as the metric, resulted in 10-7.612 of the full dose for BEI-BSO while 10-7.532 was for BEI-IFA. In conclusion, the etiologic agents of the ND outbreaks recently reported in vaccinated chickens in Malaysia were found belonging to the velogenic genotype VIIa strain. The exposure of the NDV to UVC light + riboflavin for 14 hours or the exposure of the virus to BEI treatment for 21 hours at 37oC was found to be adequate for the complete inactivation of the virus as demonstrated by its failure to induce mortality in the SPF chicken embryonated eggs, 6 days post inoculation in two successive passages. The preparation of stable water in oil emulsion from both black seed oil and incomplete Freund's adjuvant was successfully achieved in this study. An inactivated ND oil-emulsified vaccine from NDV IBS/025/13 high pathogenic viruses provides protection in young chickens against NDV IBS 002/11genotype VII virus isolate. The BEI-black seed oil and BEI- Freund’s adjuvant as well as commercial vaccine were demonstrated in this study to be capable of offering full protection against virulent NDV challenge.